2018
DOI: 10.1039/c8cc00718g
|View full text |Cite
|
Sign up to set email alerts
|

Covalent attachment of [Ni(alkynyl-cyclam)]2+ catalysts to glassy carbon electrodes

Abstract: Surface modification of glassy carbon electrodes (GCEs) with molecular electrocatalysts is an important step towards developing more efficient heterogeneous CO2 reduction materials. Here, we report direct anodic electrografting of [Ni(alkynyl-cyclam)]2+ catalysts to the surface of GCEs in one simple step using inexpensive earth-abundant chemicals. When modified, these electrodes show reversible electrochemistry in organic solvents with zero peak-to-peak separations (ΔE = 0) and non-diffusive I (V) profiles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…A more favorable way to introduce catalytic moieties to graphitic electrodes involves post-pyrolysis modifications of carbon edge and basal sites with well-defined molecular motifs. For this purpose, several creative chemical methods have been developed to immobilize molecular catalysts to the carbonbased surfaces using covalent bonds, [4][5][6][7][8][9][10][11] − stacking [12][13][14][15][16][17][18][19] and electrostatic interactions. 20,21 Carbon edge sites are often modified covalently using 'click' chemistry 4,7 or aryl radical intermediates formed from diazonium salts.…”
mentioning
confidence: 99%
“…A more favorable way to introduce catalytic moieties to graphitic electrodes involves post-pyrolysis modifications of carbon edge and basal sites with well-defined molecular motifs. For this purpose, several creative chemical methods have been developed to immobilize molecular catalysts to the carbonbased surfaces using covalent bonds, [4][5][6][7][8][9][10][11] − stacking [12][13][14][15][16][17][18][19] and electrostatic interactions. 20,21 Carbon edge sites are often modified covalently using 'click' chemistry 4,7 or aryl radical intermediates formed from diazonium salts.…”
mentioning
confidence: 99%
“…New directions and applications of anodic ethynyl deposition methods have already begun to appear. These include the depositions of a nickel cyclam complex that is an effective catalyst for CO 2 reduction, using the direct oxidation method, [5] and several calixarenes anchored through multiple ethynyl groups, using the lithio activation method. [6] Both Sheridan et al [4] and Jouikov and Simonet [7] have shown that the direct oxidation method may be successful even when the leaving group of a terminal ethynyl moiety is SiMe 3 + .…”
Section: ð2þmentioning
confidence: 99%
“…Recently it has been shown that radical‐based electrografting processes are effective in preparing chemically modified electrodes to which molecules are covalently attached through an ethynyl group . We have previously described an assortment of methods whereby metallocenes derivatized at a cyclopentadienyl ring with a terminal ethynyl group can be covalently attached to carbon surfaces .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently reported surface modification of glassy carbon electrodes for CO2 reduction with a series of [Ni(alkynyl-cyclam)] 2+ complexes, serves as an isolated example. 25 We have ongoing interests in N-propargyl cyclams as precursors for Cu(I)-catalysed azide-alkyne Huisgen 'click' reactions, which enable the introduction of more complex pendant functionality as in 4 and 5 above, [26][27][28] a strategy that has also been employed in a number of other metal chelating systems. 29…”
Section: Introductionmentioning
confidence: 99%